Stolypin’s Resettlement Policy and the Problem of the Land Issue Softening in European Russia: Assessments of the German-Speaking Russian Studies of the 20th Century - Dorozhkin, Andrey G.; Filatov, Vladimir; Tomarov, Aleksey; Kozyr, Alexandr; Velikanova, Svetlana; Chernykh, Oksana (Journal of History Culture and Art Research, 2018)
In Germanic studies of Russia, the issue of the resettlement movement to Asian Russia prospects was regarded at the beginning of the twentieth century, which became much more active during the years of the Stolypin reform, to defuse the acuteness of the agrarian issue in the European part of the empire. In this regard, the attention was drawn to the extent of migration to Siberia and to the categories of migrants. After a long break, the interest to the problem resumed in the German-speaking historiography during the 60-70s of the 20th century. The researchers of Germany, and somewhat later of Austria, paid a close attention to the factor of "back migration", the return of migrants to their former place of residence due to unfavorable circumstances, to these very unfavorable circumstances, largely in solidarity with Soviet historians during the explanation of the reasons for re-immigration. And not without the influence of the latter, the possibilities of resettlement to contribute to the mitigation of the agrarian problem in European Russia were usually considered skeptically. However, since the mid-1980s, there has been a clear overcoming of pessimistic assessments and conclusions. The Austrian historian A. Moritsch and the West German researcher D. Landgraf drew attention to the place of origin of the peasants who moved to Siberia and the Far East, analyzed the causes of "back migration" more closely, stressed that, with all the difficulties of adaptation to life in a new place, the majority of migrants still did not repatriate, which had a positive effect both for the progress of agriculture in Asian Russia, and (with all possible reservations) for the situation with the agrarian issue in the European part of the country.